TINJAUAN YURIDIS TERHADAP IZIN USAHA PENDIRIAN KAFE DI KOTA MEDAN - stephanie, winnie; Pakpahan, Kartina; Fitriyani Pakpahan, Elvira (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Business activities to establish a café require permission from Medan City government agencies. Licensing is one of the government tools as a legal tool used to control the behavior of its citizens, the permit is the approval of the authorities based on government laws or regulations, so it does not deviate from the provisions that prohibit the law. However, there are still many café business actors in Medan City who do not have licenses to carry out business activities. The focus of this research is how is the implementation of the implementation of the café establishment business license in the city of Medan?, what are the obstacles arising from the implementation of the application of a café establishment business license in the city of Medan? and how are sanctions applied to Kafes that do not have a café establishment business license in the city of Medan? The objectives of this study are to determine the implementation of the implementation of the café establishment business license in Medan City, to find out the obstacles arising from the implementation of the application of a café establishment business license in Medan City and to find out the application of sanctions against Kafes that do not have a café establishment business license in Medan City. The type of research used in the preparation of this research is a type of empirical normative legal research. This study used a data collection method which is an interview and literature research that is analyzed descriptively. The conclusion of the results of this study is business actors apply for NIB related first, NIB applications can be made through the OSS or SiCantik pages. Business actors must register business activities in TDUP. Business actors in obtaining NIB are required to register TDUP through informatics techniques made by the government in the form of a website, namely SiCantik which is made from the OSS system, with the aim of easing the burden of OSS applications so as to speed up and maximize the business activity permit process. However, there is a lack of knowledge of business actors in using electronic applications that have an online base so that business actors have difficulty in operating SiCantik. Based on Article 456 of Government Regulation No. 5 of 2021, every Business Actor who, based on the results of supervision, is found to have committed nonconformities or violations of Business Licensing in the tourism sector is subject to administrative sanctions in the form of warnings, Temporary suspension of business activities, administrative fines, and revocation of business licenses.